Partnership Based Green Economy With Kurrak Village Farming Communities in Post Harvest Coffee Processing in The Recovery of Covid-19 - Amran, Arman; Amir, Amir; Arham, Ihsan; Dewi, Suryani; Ashari, Asri Mulya; Mustadjab, Andi Zulham Azwar (STKIP Singkawang, 2023)
Kurrak Village, Polewali Mandar Regency is a coffee-producing village that has the opportunity to develop an organic coffee agro-industry to support the realization of a green economy, namely a program to improve the Indonesian economy by focusing on environmentally sound activities. Some of the problems faced by coffee farming communities in the region include how to harvest and handle post-harvest coffee. The purpose of this community service program (PKM) is to improve the ability of the Kurrak village coffee farming community in post-harvest processing and to increase the role of micro, small and medium enterprises (UMKM) in establishing partnerships with coffee farmers. The method of implementing the activity is by counseling and practice with several stages including preparation, implementation and evaluation of the program. The PKM activity was carried out in a coffee plantation for residents in Kurrak village, attended by 25 representatives of the Kurrak village community. The results of the PKM activities showed that the activity participants had the ability to apply post-harvest coffee processing techniques, the enthusiasm and motivation of the farmer members increased and they began to activate the collaboration of MSMEs and coffee farmers in Kurrak village.